The Feeling of Action Tendencies: On the Emotional Regulation of Goal-Directed Behavior - Lowe, Robert (Frontiers in Psychology, 2011)
In this article, we review the nature of the functional and causal relationship between neurophysiologically/psychologically generated states of emotional feeling and action tendencies and extrapolate a novel perspective. Emotion research, over the past century and beyond, has tended to view feeling and action tendency as independent phenomena: Attempts to outline the functional and causal relationship that exists between them have been framed therein. Classically, such relationships have been viewed as unidirectional, but an argument for bidirectionality rooted in a dynamic systems perspective has gained strength in recent years whereby the feeling-action tendency relationship is viewed as a composite whole. On the basis of our review of somatic-visceral theories of feelings, we argue that feelings are grounded upon neural-dynamic representations (elevated and stable activation patterns) of action tendency. Such representations amount to predictions, updated by cognitive and bodily feedback. Specifically, we view emotional feelings as minimalist predictions of the action tendency (what the agent is likely to do) in a given situation. The essence of this point is captured by our exposition of action tendency prediction-feedback loops (ATPFL) which we consider, above all, in the context of emotion regulation, and in particular, of emotion regulation of goal-directed behaviour. The perspective outlined may be of use to emotion theorists, computational modellers and roboticists.